Information seeking behaviour of university students in Klang Valley / Siti Nurfathehah Zulkifly - Zulkifly, Siti Nurfathehah (Faculty of Information Management, 2022)
The main goal of this study is to investigate the information seeking behaviour of university students in Klang Valley. The study attempted to determine the elements of information seeking behaviour as well as the most important element together with the elements that influence the information seeking behaviour among university students in Klang Valley. The objectives are: i) to determine the elements of information seeking behaviour among university students in Klang Valley, ii) to identify the most important element for information seeking behaviour among university students in Klang Valley and iii) to ascertain the elements that influence the information seeking behaviour among university students in Klang Valley. The data from 166 university students in Klang Valley has been collected. The research methodology and technique used to investigate this phenomenon are the quantitative approach and questionnaire instrument. The results of the data analysis were constructed using SPSS software. The results indicated there are significant relationship exist between Starting, Chaining, Browsing, Differentiating, Monitoring, Extracting and Information Seeking Behaviour.